Barrier Behaviour Analysis (BaBA) reveals extensive effects of fencing on wide‐ranging ungulates. Issue 4 (6th January 2021) - Xu, Wenjing; Dejid, Nandintsetseg; Herrmann, Valentine; Sawyer, Hall; Middleton, Arthur D.
Abstract: As human activities expand globally, there is a growing need to identify and mitigate barriers to animal movements. Fencing is a pervasive human modification of the landscape that can impede the movements of wide‐ranging animals. Previous research has largely focused on whether fences block movements altogether, but a more nuanced understanding of animals' behavioural responses to fences may be critical for examining the ecological consequences and prioritizing conservation interventions. We developed a spatial‐ and temporal‐explicit approach, Barrier Behaviour Analysis (BaBA, available as an r package), to examine individual‐level behaviours in response to linear barriers. BaBA classifies animal‐barrier encounters into six behaviour categories: quick cross, average movement, bounce, back‐and‐forth, trace and trapped . We applied BaBA to wide‐ranging female pronghorn Antilocapra americana and mule deer Odocoileus hemionus in an area of western Wyoming, USA, with >6, 000 km of fencing. We found both species were extensively affected by fences, with nearly 40% of fence encounters altering their normal movements, though pronghorn were more strongly affected than mule deer. On average, an individual pronghorn encountered fences 250 times a year—twice the encounter rate of mule deer. Pronghorn were more likely to bounce away from fences, whereas deer engaged in more back‐and‐forth, trace and average movement near fences. We aggregated these behavioural responses to demonstrate how BaBA can be used to examine species‐specific fencing permeability and to identify problematic fence segments in order to guide fence modification or removal. Synthesis and applications . Our work provides empirical evidence on how fences affect wildlife movement. Importantly, Barrier Behaviour Analysis (BaBA) can be applied to evaluate other linear features (such as roads, railways and pipelines) and habitat edges, enhancing our ability to understand and mitigate widespread barrier effects to animal movement. Abstract : Our work provides empirical evidence on how fences affect wildlife movement. Importantly, Barrier Behaviour Analysis (BaBA) can be applied to evaluate other linear features (such as roads, railways and pipelines) and habitat edges, enhancing our ability to understand and mitigate widespread barrier effects to animal movement. 摘要: 随着人类活动在全球范围内持续扩张, 生态学家需要识别动物迁移障碍并缓解其影响。作为一种普遍存在的人类改造景观的方式, 围栏严重限制了广域活动物种的迁移。此前研究大多关注围栏是否完全阻断了动物迁移, 但忽略了围栏可能造成的其他行为反应。这些反应可能对量化围栏的生态后果及优化保育策略至关重要。 我们研发了一种基于时空数据来衡量个体对线状障碍行为反应的方法, 称为障碍行为分析 (BaBA, 可通过R 包获取) 。BaBA将动物‐障碍相遇事件划分成六种类型: 快速跨越, 日常活动, 反弹, 徘徊, 追踪, 以及围困。我们应用BaBA分析了美国怀俄明州西部的雌性叉角羚 Antilocapra americana 和骡鹿 Odocoileus hemionus 的迁移活动。该区域围栏总长度超过6000千米。 我们发现两个物种都广泛受到了围栏影响, 接近40%的围栏相遇事件改变了动物的正常迁移活动。叉角羚受到的影响较骡鹿更大。每只叉角羚平均每年遇到围栏250次, 是骡鹿的两倍。骡鹿在围栏边表现出更多的徘徊, 追踪, 及日常活动, 而叉角羚更可能从围栏反弹。 综合这些行为反应, 我们展示了如何使用BaBA来量化特定物种的围栏可通过性, 并以此鉴别对动物迁移影响较大的围栏段, 来指导围栏改造或移除。 总结和应用: 本研究为理解围栏如何影响野生动物迁移提供了实验证据。更重要的是, BaBA适用于研究动物对其他线状障碍 (如道路, 铁路, 和运输导管) 和生境边界的行为反应。这些应用可以促进我们理解障碍效应如何作用于动物行为, 并提出相应的缓解办法。